2021
DOI: 10.33225/pec/21.79.360
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Students’ Academic Achievement

Abstract: Emotional Intelligence (EI) is essential attribution among school learners of today. In this respect, determination and normalization of the measures to investigate and recognize dimensions levels help educators have a successful intervention and increase students' academic achievement level. This research aimed to explore the relationship between Emotional Intelligence (EI) and the academic achievement of Arabic basic school students in China. Further, it also sought to determine the level of students' emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Emotional intelligence is one of the essential factors that support children's achievements, both in school and in their future careers. Parents and educators must understand and provide learning experiences that can develop students' emotional intelligence early on [9], [12]. The researchers realized that in addition to cognitive intelligence, this emotional intelligence is so crucial that students with sound intelligence tend to be successful in learning and have a good personalities.…”
Section: Resultsmentioning
confidence: 99%
“…Emotional intelligence is one of the essential factors that support children's achievements, both in school and in their future careers. Parents and educators must understand and provide learning experiences that can develop students' emotional intelligence early on [9], [12]. The researchers realized that in addition to cognitive intelligence, this emotional intelligence is so crucial that students with sound intelligence tend to be successful in learning and have a good personalities.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a recent study among Arabian students in China by AL-Qadri and Zhao (2021) proved that EI was a significant predictor of students’ AO, with statistically significant differences between male and female students’ EI scores, AO level and LM; in favor of the female students, which is not in line with the current study. [ 43 ] Gender differences may be explained by the difference in the age group where AL-Qadri and Zhao's study was conducted among school students besides the smaller sample size (303 students) than the current study and the higher number of female students than their male counterparts.…”
Section: Discussionmentioning
confidence: 77%
“…This study confirmed previous findings ( Yenice et al, 2018 ; Rodriguez-Gonzalez et al, 2021 ). Emotional intelligence is an essential psychological ability, which supports and influences college students’ learning ( AL-Qadri and Zhao, 2021 ). Students need a certain level of emotional regulation capabilities if they are to maintain good motivation.…”
Section: Discussionmentioning
confidence: 99%